The Shpetian Circle in the Work on GAKhNʼs Encyclopedia - Avanesian, Alina (Wiener Slawistischer Almanach, 2026)
The article examines a group of philosophical entries in the GAKhN’s Encyclopedia of Artistic Terminology. It focuses on authors associated with Gustav Shpet’s intellectual milieu and analyses the theoretical orientation they introduced into the Encyclopedia. The study reconstructs three conceptual domains through which this orientation becomes visible. A phenomenological perspective appears in the critique of psychologism and in the analysis of aesthetic acts such as contemplation and fantasy, which opens onto the problem of myth as a broader configuration of consciousness. Hermeneutic approach become visible in reflections on interpretation, tradition, and the internal organisation of meaning, articulated through Shpet’s concept of inner form. Finally, the semiotic entries on sign, meaning, and sense clarify the distinctions between these concepts and their role in the analysis of aesthetic experience.